Creating Conditions for Effective Public Investment Sub-national Capacities in a Multi-level Governance Context - Mizell, Lee (OECD Regional Development Working Papers, 2013)
Growth and jobs are top concerns for policy makers confronting difficult economic conditions in many OECD countries. Sub-national governments are important contributors to national growth, but in many cases their economies are struggling as well. Faced with tight fiscal conditions, all levels of government must achieve policy goals with fewer resources. This is particularly true for public investment, a potentially growth-enhancing form of public expenditure which numerous governments are reducing to meet other (current) financial obligations. Even where public investment is stable or increasing, governments may want to improve returns to public and private investment. On average, nearly two-thirds of public investment in OECD countries occurs at the sub-national level. Clearly then, any discussion of improving returns to investment must address the capacities of sub-national governments to invest effectively. Unfortunately, the implementation of recovery packages across OECD countries revealed that both national and sub-national actors may lack the appropriate tools and governance arrangements to make the best use of investment funds. Taking this finding as its starting point, this paper seeks to 1) identify capacities that enable sub-national governments to design and implement sound public investment strategies for regional development, and 2) provide practical guidance for assessing and strengthening these capacities in a context of multi-level governance